1978
DOI: 10.1177/073088847800500402
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Work and Nonwork

Abstract: A sample of 178 individuals was asked to describe their work experiences, nonwork experiences, and their self-concept using the same set of 25 semantic differential scales. The same individuals also provided information regarding some limited aspects of their nonwork behavior. Comparisons of the semantic differential descriptions permitted each individual to be classified into one of the following four types: Spillover- Work-oriented, Spillover-Nonwork-oriented, Compensatory-Work-oriented, and Compensatory-Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(13 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…There is considerable opinion and evidence in the literature that work does not exist separate from personal life realms (Champoux, 1978(Champoux, , 1980Clark, 2000;Cohen, 1997aCohen, , 1997bCrooker, Smith, & Tabak, 2002;Crouter, 1984;Fredriksen-Goldsen & Scharlach, 2001;Greenhaus & Beutell, 1985;Hochschild, 1997;Kanter, 1977;Kelly & Kelly, 1994;Kirchmeyer, 1993Kirchmeyer, , 1995Lance & Richardson, 1988;Lewis, Rapoport, & Gambles, 2003;Near et al, 1980;Watkins & Subich, 1995;Wilensky, 1960). This relationship of work, home, and leisure has been described by the crossing of life realm boundaries where individuals balance life realms and life roles by crossing the permeable, flexible borders between them (Ashforth, Kreiner, & Fugate, 2000;Clark, 2000;Hall & Richter, 1988).…”
Section: Literature Reviewmentioning
confidence: 95%
“…There is considerable opinion and evidence in the literature that work does not exist separate from personal life realms (Champoux, 1978(Champoux, , 1980Clark, 2000;Cohen, 1997aCohen, , 1997bCrooker, Smith, & Tabak, 2002;Crouter, 1984;Fredriksen-Goldsen & Scharlach, 2001;Greenhaus & Beutell, 1985;Hochschild, 1997;Kanter, 1977;Kelly & Kelly, 1994;Kirchmeyer, 1993Kirchmeyer, , 1995Lance & Richardson, 1988;Lewis, Rapoport, & Gambles, 2003;Near et al, 1980;Watkins & Subich, 1995;Wilensky, 1960). This relationship of work, home, and leisure has been described by the crossing of life realm boundaries where individuals balance life realms and life roles by crossing the permeable, flexible borders between them (Ashforth, Kreiner, & Fugate, 2000;Clark, 2000;Hall & Richter, 1988).…”
Section: Literature Reviewmentioning
confidence: 95%
“…A segmentation model has been added in which life activities away from work are assumed to be independent of job activities (see Kabanoff and O'Brien, 1980). The three models are based on the similarity or dissimilarity in behaviours and activities at work and away from work (Champoux, 1978), with all three receiving some empirical support (Kabanoff and O'Brien, 1980). Rather than assuming the traditional focus on the similarity of work and nonwork activities, role theory permits an examination of the importance of, and effort devoted to, multiple roles.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Traditionally, work life is thought to dominate the weekday, whereas home, family, and leisure interests play a larger role on weeknights and weekends. Many have suggested that this is not the case in practicethat work, home, and leisure life realms overlap and do not exist as separate entities (Champoux, 1978;Clark, 2000;Crouter, 1984;Kanter, 1977;Watkins & Subich, 1995;Wilensky, 1960), and empirical research supports this claim (Champoux, 1980;Cohen, 1997aCohen, , 1997bKirchmeyer, 1993;Lance & Richardson, 1988). For example, some research suggests the benefits of recognizing that a person's outside-work identity spills into their job (Bond et al, 1998) and recommends relating to employees as individuals rather than just as workers (Friedman et al, 2000).…”
mentioning
confidence: 99%